2020
DOI: 10.3390/cells9051153
|View full text |Cite
|
Sign up to set email alerts
|

hiPSC-Derived Cardiomyocyte Model of LQT2 Syndrome Derived from Asymptomatic and Symptomatic Mutation Carriers Reproduces Clinical Differences in Aggregates but Not in Single Cells

Abstract: Mutations in the HERG gene encoding the potassium ion channel HERG, represent one of the most frequent causes of long QT syndrome type-2 (LQT2). The same genetic mutation frequently presents different clinical phenotypes in the family. Our study aimed to model LQT2 and study functional differences between the mutation carriers of variable clinical phenotypes. We derived human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM) from asymptomatic and symptomatic HERG mutation carriers from the same f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…The authors of the study suggested the importance of considering the clinical differences in phenotypes observed in single and aggregate hiPSC-CMs, particularly when conducting preclinical drug toxicity tests. 203 …”
Section: Novel Strategies To Study Ion Channel Dysfunction and Drug-specific Therapies In Lqt1 Lqt2 And Lqt3 Syndromesmentioning
confidence: 99%
“…The authors of the study suggested the importance of considering the clinical differences in phenotypes observed in single and aggregate hiPSC-CMs, particularly when conducting preclinical drug toxicity tests. 203 …”
Section: Novel Strategies To Study Ion Channel Dysfunction and Drug-specific Therapies In Lqt1 Lqt2 And Lqt3 Syndromesmentioning
confidence: 99%
“…They also found that iPSC-CM aggregates from symptomatic patients, compared to asymptomatic patients, were more arrhythmic on rapid (IKr) and slow (IKs) delayed rectifier potassium channel blocks. This data suggests that this in-vitro human iPSC-CM model recapitulates major phenotype characteristics observed in LQT2 mutation carriers [ 27 ].…”
Section: Stem Cell-based Disease Modelingmentioning
confidence: 73%
“…This Special Issue includes both research [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] and reviews articles [ 10 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] which cover wide ranges of stem cell research: adult stem cells, cancer stem cells, pluripotent stem cells, and complex 3D organoid/cell aggregate models [ 26 , 27 , 33 ], with the focuses on stem cell biology/technology [ 10 , 23 , 24 , 25 , 26 , 31 , 32 , 34 ], and stem cell-based disease modeling [ 10 , 27 , 29 , 31 , 33 , 38 , 43 ] and cell therapy [ 24 , 28 , 30 , 32 , 35 , 36 , 37 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of 3D cardiac models per se has also been proved to benefit cardiac disease modeling studies. EHT constructs [ 88 , 116 , 117 , 118 ] and 3D cultured hPSC-CMs [ 119 ] have been successfully used to recapitulate cardiac disease phenotypes, showing in some cases that the use of more complex cardiac models can benefit and improve the liability of the outcomes taken from disease modeling studies. Specifically, Goldfracht and colleagues, who studied catecholaminergic polymorphic ventricular tachycardia type 2 (CPVT2) and long QT syndrome type 2 (LQTS2) disorders using patient-derived hPSC-CMs in an EHT model, showed that the arrhythmogenic potential of the generated CPVT2 and LQTS2 tissues was reduced in EHT constructs, compared with the same cells within single-cell models [ 88 ], being more similar to what occurs in vivo.…”
Section: In Vitro Applications Of Hpsc-derived 3d Cardiac Microtismentioning
confidence: 99%
“…In the EHT-HCM model, it was possible to recapitulate several hallmarks of the disease including prolonged AP duration, increased contractility and hypertrophy. Also, upon modeling of LQTS2 cardiac disorder, Shah and co-workers revealed that clinical phenotypic differences observed in patients with this disease were also observed in hiPSC-CMs cultures as 3D aggregates but were not seen in homogenous cultures of hPSC-CMs, reinforcing the utility and necessity of more complex cardiac models in this field [ 119 ].…”
Section: In Vitro Applications Of Hpsc-derived 3d Cardiac Microtismentioning
confidence: 99%